2017
DOI: 10.17138/tgft(5)85-93
|View full text |Cite
|
Sign up to set email alerts
|

Weeds alter the establishment of Brachiaria brizantha cv. Marandu

Abstract: Weeds alter the establishment of Brachiaria brizantha cv. Marandu Malezas afectan el establecimiento de AbstractThe present study evaluated the effects of different periods of coexistence among the main weeds and Marandu brachiaria grass (Brachiaria brizantha, now Urochloa brizantha) in newly sown pasture. The experiment was conducted in a randomized block with 4 replications, with treatments being 8 coexistence periods: 0, 15, 30, 45, 60, 75, 90 and 120 days after emergence. A phytosociological assessment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
25
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 3 publications
5
25
0
3
Order By: Relevance
“…It´s noted that the grasses of the genus Urochloa (syn. Brachiaria) are among the exotic forages currently cultivated in Brazilian pastures due to their adaptation to the most adverse climatic and soil conditions, dominating widely on the other genera of forages used in the Cerrado environment (MARCHI et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It´s noted that the grasses of the genus Urochloa (syn. Brachiaria) are among the exotic forages currently cultivated in Brazilian pastures due to their adaptation to the most adverse climatic and soil conditions, dominating widely on the other genera of forages used in the Cerrado environment (MARCHI et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The main problem caused by weeds is the direct competition for space, light, water, and nutrients, causing a reduction of the physiological reserves of forages (SANTOS et al, 2011). When competing for growth factors, weeds can also provide decreases in the nutritional value and pasture support capacity, provide an increase in the time of pasture formation and recovery, cause injury and/or intoxication to animals, and compromise the aesthetics of the property (MARCHI et al, 2017;BELLÉ et al, 2018;MARCHI et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…), rye (Secale cereal), barley (Hordeum vulgare), maize (Zea mays) and wheat (Triticum aestivum) (Bailey & Eijnatten 1961, Igarashi et al 1986, Urashima et al 1993 ABSTRACT RESUMO al. 1996, Couch & Kohn 2002, Goulart et al 2003, Couch et al 2005, Marchi et al 2005. The adoption of the Pyricularia oryzae designation as the species associated with blast disease is recent.…”
Section: Introductionmentioning
confidence: 99%
“…The adoption of the Pyricularia oryzae designation as the species associated with blast disease is recent. Until the early 2000s, Pyricularia grisea was considered the pathogen of blast disease on rice, signal grass, barley and wheat (Urashima et al 1993, Marchi et al 2005. A molecular phylogenetic reclassification proposed by Couch & Kohn (2002) showed that P. grisea was exclusively associated with blast disease on grasses from the Digitaria genus, whereas P. oryzae was associated with rice, wheat and other cultivated grasses or invasive plants (e.g.…”
Section: Introductionmentioning
confidence: 99%